2014
DOI: 10.1111/iwj.12249
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of toe amputation in patients with type 2 diabetes in Tianjin, China

Abstract: The aim of this study is to determine the predictors for reulceration, reamputation and mortality in patients with diabetes following toe amputation, and the impact of activities of daily living on clinical outcomes. This prospective cohort study included 245 patients who had undergone toe amputation (202 healing and 43 non-healing) and was followed for a 5-year period. Data regarding new foot ulceration, reamputation and mortality were recorded, and the patients' activities of daily living were evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…Older age was a risk factor for mortality on multivariable analysis. Increased mortality with age has been previously reported among patients with diabetic foot ulceration – after toe amputation for a diabetic foot – and in patients with DFI in the context of chronic kidney disease . Increased age‐related comorbidities may play a role, as may the recognised poorer outcomes after amputation in the elderly .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Older age was a risk factor for mortality on multivariable analysis. Increased mortality with age has been previously reported among patients with diabetic foot ulceration – after toe amputation for a diabetic foot – and in patients with DFI in the context of chronic kidney disease . Increased age‐related comorbidities may play a role, as may the recognised poorer outcomes after amputation in the elderly .…”
Section: Discussionmentioning
confidence: 95%
“…Increased mortality with age has been previously reported among patients with diabetic foot ulcerationafter toe amputation for a diabetic footand in patients with DFI in the context of chronic kidney disease. 14,20,21 Increased age-related comorbidities may play a role, as may the recognised poorer outcomes after amputation in the elderly. 21,22 In our study, only two (0.5%) patients had major amputation as their initial procedure, and only 11 (2.7%) had a previous major amputation, limiting any conclusion that may have been drawn regarding outcomes after previous or initial major amputation level.…”
Section: Discussionmentioning
confidence: 99%
“…There are many complications that affect people with diabetes, the foot ulcer complications take lead [9]. According to Chu and Wang [10], some patients developed foot ulcer after 1, 3, and 5 years and when their prevalence was examined they were increasing from 27.3%, 57.2%, and 76.4%, respectively, this also led to increase in prevalence of foot amputations at 12.5%, 22.3%, and 47.1% respectively [10]. Other studies showed that the mortality rate as a result of diabetic foot amputation ranges from 13% to 40% within one year, at 3 years it was ranging from 35% to 65%, and at 5 years it was ranging from 39% to 80%, which was found to be worse than the mortality rate for most cancers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Both single and multiple toe amputation lead to deformities and alter foot function, increasing the risk of development of new ulceration . Although location and level of amputation have been also related to high probability of reulceration , until recently , there has been no proposal of a simple algorithm that embraces all variables.…”
Section: Introductionmentioning
confidence: 99%
“…Both single and multiple toe amputation lead to deformities and alter foot function, increasing the risk of development of new ulceration (5,6). Although location and level of amputation have been also related to high probability of reulceration (7)(8)(9)(10), until recently (11), there has Key Message • transfer lesions are a common situation after minor amputation that may be extremity or life-threatening, increasing the health care cost • this is an assessment of reulceration risk using Miller's formula in 156 consecutive records of participants with diabetes and a history of amputation • one amputation more than first segment amputation shows the highest risk of reulceration between patients with previous forefoot amputations been no proposal of a simple algorithm that embraces all variables. Miller et al (11) distinguished between patients who have undergone one or more forefoot amputations, those who had an appropriate foot function and a low likelihood of reulceration and those who will probably develop a new ulcer and will undergo revisional surgery.…”
Section: Introductionmentioning
confidence: 99%